2016
DOI: 10.1016/j.bbrc.2015.11.134
|View full text |Cite
|
Sign up to set email alerts
|

Rad6 upregulation promotes stem cell-like characteristics and platinum resistance in ovarian cancer

Abstract: Ovarian cancer is the fifth most deadly cancer in women in the United States and despite advances in surgical and chemotherapeutic treatments survival rates have not significantly improved in decades. The poor prognosis for ovarian cancer patients is largely due to the extremely high (80%) recurrence rate of ovarian cancer and because the recurrent tumors are often resistant to the widely utilized platinum-based chemotherapeutic drugs. In this study, expression of Rad6, an E2 ubiquitin-conjugating enzyme, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…UBE2A and UBE2B are two RAD6 homologs originally identi ed in yeast and required for DNA repair [31]. They are both upregulated in OC compared to normal ovarian tissues, and their high expression is associated with poor prognosis in OC patients [6]. Downregulation of RAD6 was previously found to reduce the expression of the cancer stem cell markers, ALDH1A1 and SOX2, and to increase the sensitivity of OC cells to carboplatin [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UBE2A and UBE2B are two RAD6 homologs originally identi ed in yeast and required for DNA repair [31]. They are both upregulated in OC compared to normal ovarian tissues, and their high expression is associated with poor prognosis in OC patients [6]. Downregulation of RAD6 was previously found to reduce the expression of the cancer stem cell markers, ALDH1A1 and SOX2, and to increase the sensitivity of OC cells to carboplatin [32].…”
Section: Discussionmentioning
confidence: 99%
“…The UBE2 family is composed of 40 members, which are considered as pivotal factors in the ubiquitination cascade [5]. Some studies have reported that aberrant expression of UBE2s in tumors has an impact on tumor prognosis, suggesting that UBE2s are informative tumor markers for early diagnosis and prediction of prognosis [6][7][8]. However, the biological role and action mechanism of these enzymes in OC have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…3 Our previous work has shown a connection between RAD6 expression and chemoresistance and acquisition of a stem cell-like phenotype in ovarian cancer cell lines. 4 In our manuscript we followed up on these findings and showed that RAD6 levels are high in ovarian cancer and increase in response to treatment with chemotherapeutic agents in ovarian cancer cell lines as well as patient tumors. 1 Mortality in ovarian cancer patients is typically attributed to development of a recurrent, chemoresistant tumor following chemotherapy and RAD6 correlated with progression free survival (PFS) in ovarian cancer patients.…”
mentioning
confidence: 85%
“…RAD6 is overexpressed in melanoma and breast cancer where it correlates with tumor development, progression and metastasis 13 – 15 . Our recent studies showed increased expression of RAD6 in ovarian tumors and its levels correlated with progressive disease 16 . In OC cell lines, RAD6 expression promoted development of a stem cell-like phenotype and resistance to carboplatin 16 .…”
Section: Introductionmentioning
confidence: 91%